Comment de futurs enseignants conçoivent le numérique : le projet Ambassadeurs du numérique de l’académie de Paris - Laurent Petit; Aude Seurrat (Humanités Numériques)
Our article is the result of a research project conducted within the Humane workgroup (« Digital Humanities, between research and education », a groupe thématique numérique or GTnum of the French ministry of Education: the Ambassadeurs du numérique (Digital Ambassadors) project of the Paris regional academic council. The implementation of workshops with the student trainees participating in the programme allows us to question how they approach digital technologies and the role these technologies play in their developing professional identities. This article shows therefore the specific impact of digital humanities in teacher training.